Nanoscale physico-mechanical properties of an aging resistant ZTA composite. (November 2021) - Benalcázar Jalkh, E.B.; Coelho, P.G.; Witek, L.; Bergamo, E.T.P.; Lopes, A.C.O.; Monteiro, K.N.; Cesar, P.F.; Genova, L.A.; Lisboa-Filho, P.N.; Abreu, J.L.B.; Campos, T.M.B.; Canteenwala, A.; et al.
Abstract: Objective: To characterize the effects of aging on the nanomechanical properties and 3D surface topographical parameters of an experimental Zirconia Toughened Alumina (ZTA) composite compared to its respective individual counterpart materials. Methods: Disk-shaped specimens comprised of three material groups were processed: 1) ZTA 70/30 (70% alumina reinforced with 30% second-generation 3Y-TZP); 2) Zpex (Second-generation 3Y-TZP), and; 3) Al2 O3 (High purity Alumina) (n = 10/material, 12 × 1 mm). After synthesis, ceramic powders were pressed, the green-body samples were sintered and polished. Nanoindentation testing was performed to record elastic modulus (E) and hardness (H). Interferometry was utilized to assess 3D surface roughness parameters (Sa, Sq ), while X-ray diffraction (XRD) and scanning electron microscope (SEM) assessed the crystalline content and microstructure. All tests were performed before and after simulated aging (134°C, 2.2 bar, 20 h). Statistical analyses were performed using linear mixed-model and least square difference pos-hoc tests (α = 5%). Results: XRD spectra indicated increase of monoclinic peaks for Zpex (~18%) relative to ZTA 70/30 (~2.5%) after aging. Additionally, aging did not affect the surface roughness parameters of ZTA 70/30 and Al2 O3, although a significant increase in Sa was recorded for Zpex following aging (~90 nm) ( p  < 0.001). Al2 O3 yielded the highest H and E values (H:21 GPa, E: 254 GPa), followed by ZTA 70/30 (H: 13 GPa, E: 214 GPa) and Zpex (H:11 GPa, E: 167 GPa), all significantly different ( p  < 0.03). Conclusion: ZTA 70/30 and Al2 O3 presented high hydrothermal stability with respect to all evaluated variables, where artificial aging significantly increased the monoclinic content and surface roughness of Zpex.